Presentación inusual de la enfermedad de Pott: reporte de un caso - Ana Silva Rocha; Marina Henriques Mendes (Galicia Clínica)
A 63-year-old male was admitted with a 2-week-history of chest wall swelling with no accompanying symptoms, except for chronic lumbago. He had been diagnosed with bladder urothelial carcinoma and underwent transurethral-resection and BCG-instillation the year before. Physical examination and lab work was unremarkable except for an ovaloid-lump of approximately 9cm on the anterior-left chest wall[Figure-1] and elevated C-reactive protein and erythrocyte-sedimentation-rate. A CT-scan revealed other abscesses: on the right cardiophrenic recess[Figure-2] and prevertebral at L4-L5 level[Figure-3]. MRI confirmed the diagnosis of spondylodiscitis[Figure-4]. HIV-serology was non-reactive, blood-cultures were negative, abscess’ pus was amicrobian but Ziehl–Neelsen stain and M.tuberculosis detection by molecular biology were positive. The diagnosis of Pott’s disease with multiple cold abscesses was stablished. Anti-tuberculosis treatment with isoniazid, rifampin, ethambutol and pyrazinamide was started. Surgical treatment was not considered due to his stability. He was discharged and referred to the national tuberculosis control program for continuation of treatment. On the follow-up consultation, within four weeks, he had clinical improvement[Figure-5].